2006
DOI: 10.1007/s11102-006-9079-5
|View full text |Cite
|
Sign up to set email alerts
|

Complex Rhythmicity of Growth Hormone Secretion in Humans

Abstract: To better characterize the 24 hr GH secretion pattern in humans, we studied frequently sampled 24 hr GH profiles in 93 young (18-45 years of age) healthy, fed volunteers: men (n=67) and women (n=26) with BMI<26 kg/m(2). Analysis of the composite GH series in men revealed 3 significant GH "waves" with peaks occurring at midnight (p<0.0001), at noon (p<0.02) and at 1800 h (p<0.0001). In women, similar pattern was seen, with three GH "waves" peaking at midnight (p<0.0001), 1100 h (p<0.02) and at 1600 h (p<0.002).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
4
22
0
Order By: Relevance
“…Figure 1A shows the mean composite profile of lntransformed ratios of the hourly mean over daily median for the control group. The analysis of the daytime GH secretion in this group shows the presence of a statistically significant (P Ͻ .001) 3-wave GH secretion pattern, as previously demonstrated elsewhere (13). The maximal ratios occurred at 1200 PM, at 5:00 PM, and, most prominently, at 1:00 AM.…”
Section: Descriptive Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…Figure 1A shows the mean composite profile of lntransformed ratios of the hourly mean over daily median for the control group. The analysis of the daytime GH secretion in this group shows the presence of a statistically significant (P Ͻ .001) 3-wave GH secretion pattern, as previously demonstrated elsewhere (13). The maximal ratios occurred at 1200 PM, at 5:00 PM, and, most prominently, at 1:00 AM.…”
Section: Descriptive Analysissupporting
confidence: 84%
“…In a small sample of treated and untreated acromegalic patients with relatively homogeneous GH outputs, we have previously suggested the persistence of the nocturnal GH augmentation (12). Subsequently we have shown that the rhythmicity of GH secretion in humans is much more complex than a simple presence of the so-called nocturnal augmentation and consists of 3 distinct major waves of GH output, at 11:00 AM/12:00 PM, at 4:00 PM/5:00 PM, and 12:00/2:00 AM, with a sexually dimorphic pattern (13).…”
mentioning
confidence: 92%
“…This phenomenon could be possibly explained by the role of estrogens. It could also be related to a well-known physiological pattern of GH, which is released largely at night in complex ultradian pulses that do not readily follow a classic circadian pattern (10). Indirectly, the clock system directs secretion through slow-wave sleep which is strongly associated with GH release, although the precise mechanism of circadian influence is not understood.…”
Section: -Sulfatoxymelatonin In Gh Deficient Adultsmentioning
confidence: 99%
“…GH is released largely at night in complex ultradian pulses that do not readily fit a classic circadian pattern. Indirectly, the clock system directs secretion through slow-wave sleep, which is strongly associated with GH release, although the precise mechanism of circadian influence is not understood (10). We have demonstrated in a recent paper decreased 6-sulphatoxymelatonin (6-SM) excretion in male GH-deficient children and adolescents (11).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with hypertensive heart disease exhibited a greater increase in PRA during sleep-time as compared to normotensive patients (Tuck et al, 1985). Finally, growth hormone secretion by the anterior pituitary gland is pulsatile and has a circadian rhythm with the highest peak occurring at midnight (Surya et al, 2006). Growth hormone is involved in regulation of cardiac metabolism and contractility, reviewed by (Volterrani et al, 2000).…”
Section: Sleep-time Hormonesmentioning
confidence: 99%